Pengaruh Kekurangan Nutrisi Terhadap Perkembangan Sistem Saraf Anak - Papotot, Gianfranco S.; Rompies, Ronald; Salendu, Praevilla M. (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: In developing countries malnutrition contributes to high mortality rates. Children's age, previous birth spacing, mother's educational status, wealth status, and area are factors that are independently related to children's nutritional status. The first thousand days of life are a critical period for children's neurodevelopment. Physical growth, cognitive function of the brain, physiological function and changes in immune response can be impaired due to lack of nutrition at an early age. In developing countries children under 5 years have a prevalence of about 27% of malnutrition. The research objective was to determine the relationship and effect of nutritional deficiencies on the development of the nervous system in children. This research is in the form of a literature review. Literature is taken from three databases, namely PubMed, ClinicalKey and Google Scholar. The keywords used were undernutrition AND neurological disorders AND children. After being selected with inclusion and exclusion criteria, we obtained 10 literature consisting of ten cross-sectional studies. The results showed that 10 literature examined the relationship and effect of nutritional deficiencies on the development of the nervous system in children. In conclusion, nutritional deficiencies and nervous system disorders in children have an interplay of relationships. Children who suffer from nutritional deficiencies have an influence on the development of the nervous system and the most on motor and cognitive disorders.Keywords: undernutrition, neurological disorders, childrenÂ Â Abstrak: Di negara berkembang kekurangan gizi memberikan kontribusi terhadap tingginya rata-rata angka kematian. Usia anak-anak, jarak kelahiran sebelumnya, status pendidikan ibu, status kekayaan, dan wilayah merupakan faktor yang secara independen terkait dengan status gizi anak-anak. Seribu hari pertama kehidupan merupakan masa kritis bagi perkembangan saraf anak. Pertumbuhan fisik, fungsi kognitif otak, fungsi fisiologis dan perubahan respon imun bisa terganggu karena kurangnya gizi di usia dini. Di negara berkembang anak di bawah 5 tahun memiliki prevalensi sekitar 27% kekurangan gizi. Tujuan Penelitian untuk mengetahui hubungan dan pengaruh kekurangan nutrisi pada perkembangan sistem saraf anak. Penelitian ini dalam bentuk literature review. Literatur diambil dari tiga database yaitu PubMed, ClinicalKey dan Google Scholar. Kata kunci yang digunakan yaitu undernutrition AND neurological disorders AND children. Setelah diseleksi dengan kriteria inklusi dan ekslusi, didapatkan 10 literatur yag terdiri dari sepuluh penelitian cross-sectional study. Hasil penelitian menunjukan 10 literatur meneliti hubungan dan pengaruh kekurangan nutrisi terhadap perkembangan sistem saraf anak. Sebagai simpulan, kekurangan nutrisi dan kelainan sistem saraf pada anak memiliki hubungan yang saling memengaruhi satu sama lain. Anak yang mengalami kekurangan nutrisi memiliki pengaruh pada perkembangan sistem saraf dan terbanyak pada kelainan motorik dan kognitif.Kata Kunci: undernutrition, neurological disorders, children